Harnessing Epigenetics And Nanobiotechnology For Precision Medicine: Revolutionizing Stem Cell Therapy. - Bangash, Sudhair Abbas; Ririe, Avrina Kartika; Sarwar, Mehvish (Journal of Neonatal Surgery, 2025)
Purpose:The purpose of this study is to explore the integration of epigenetics and nanobiotechnology in advancing precision medicine, with a particular focus on their application in stem cell therapy. The study aims to assess the awareness, perceptions, and experiences of individuals regarding the potential of these technologies in revolutionizing stem cell-based treatments. Aim:The aim of this research is to evaluate the level of familiarity with epigenetics and nanobiotechnology, measure the perceived effectiveness of these technologies in stem cell applications, and identify the ethical concerns and barriers to their widespread implementation. Approach:A mixed-methods approach was employed to collect both quantitative and qualitative data. A survey consisting of Likert-scale and open-ended questions was administered electronically to 140 participants from diverse backgrounds, including researchers, healthcare professionals, and the general public. The survey assessed demographic information, familiarity with epigenetics and nanobiotechnology, their potential applications in stem cell therapy, ethical concerns, and the future outlook on these technologies. Methods:The data was collected using a structured questionnaire that included sections on demographic details, awareness of epigenetics and nanobiotechnology, potential applications in stem cell therapies, ethical considerations, and future outlook. The data was analyzed using descriptive statistics for the quantitative data and thematic analysis for the qualitative data to identify key themes and patterns in participants’ responses. Results:The results revealed that a significant proportion of respondents were familiar with epigenetics and nanobiotechnology, and most were optimistic about their potential in advancing stem cell therapies. Ethical concerns regarding gene editing and the accessibility of treatments were prominent, while public perception and regulatory challenges were identified as major barriers to implementation. Findings:The findings indicate strong support for the use of epigenetics and nanobiotechnology in precision medicine, with particular emphasis on stem cell differentiation and personalized medicine. However, the ethical implications and potential risks of gene editing and nanobiotechnology must be carefully managed to ensure responsible application. Theoretical and Practical Implications: The study contributes to the theoretical understanding of how epigenetics and nanobiotechnology can reshape stem cell therapies by providing insight into public perceptions, ethical concerns, and the potential for personalized treatments. Practically, the findings highlight the need for better regulatory frameworks and public education to facilitate the acceptance and responsible use of these technologies. Originality/Value:This study is one of the first to comprehensively evaluate the perceptions and experiences of individuals regarding the integration of epigenetics and nanobiotechnology in stem cell therapy. The research provides valuable insights into the challenges and opportunities these technologies present for the future of precision medicine